L’IMPACT DE L’ELECTRIFICATION EN MILIEU RURAL DANS LA REGION DE L’AGNEBY - Lazare, Atta Koffi; Téré, Gogbe; Kouamé, Tano (European Scientific Journal, ESJ, 2013)
Electrification is a collective supply that modernizes rural areas. It favours quantitative and qualitative building development of the villages. It creates basis socioeconomic supplies too. Electrification brought about economic supplies in the Agnéby rural area. It also permits liveliness and economic development in the villages. The biggest villages in the Agnéby are more equipped than the smallest ones. This imbalance is due to the population number and the civil servants’ activities who invest more in the building domain. Electrification facilitates also rural population and thank to the comfort, security, well-being and education that it offers. It is supply which brings about economic activities that help rural population, above all housewives to get out of poverty by practising retail trade. This type of trade is the most profitable economic activity in these villages.